Controlled Release of Metformin Hydrochloride from Core-Shell Nanofibers with Fish Sarcoplasmic Protein - YILMAZ, BETÜL; SENNAROĞLU BOSTAN, MÜGE (MDPI, 2019)
Background and Objectives: A coaxial electrospinning technique was used to produce core/shell nanofibers of a polylactic acid (PLA) as a shell and a polyvinyl alcohol (PVA) containing metformin hydrochloride (MH) as a core. Materials and Methods: Fish sarcoplasmic protein (FSP) was extracted from fresh bonito and incorporated into nanofiber at various concentrations to investigate the influence on properties of the coaxial nanofibers. The morphology, chemical structure and thermal properties of the nanofibers were studied. Results: The results show that uniform and bead-free structured nanofibers with diameters ranging from 621 nm to 681 nm were obtained. A differential scanning calorimetry (DSC) analysis shows that FSP had a reducing effect on the crystallinity of the nanofibers. Furthermore, the drug release profile of electrospun fibers was analyzed using the spectrophotometric method. Conclusions: The nanofibers showed prolonged and sustained release and the first order kinetic seems to be more suitable to describe the release. MTT assay suggests that the produced drug and protein loaded coaxial nanofibers are non-toxic and enhance cell attachment. Thus, these results demonstrate that the produced nanofibers had the potential to be used for diabetic wound healing applications.
Keywords: coaxial electrospinning; fish sarcoplasmic protein; nanofibers; wound healing; ELECTROSPUN NANOFIBERS; POLYMERIC NANOFIBERS; DELIVERY; FIBERS; MATRICES